2006
DOI: 10.14214/sf.335
|View full text |Cite
|
Sign up to set email alerts
|

Effect of data acquisition accuracy on timing of stand harvests and expected net present value

Abstract: Modern remote sensing provides cost-efficient spatial digital data that are more accurate than before. However, the influence of increased accuracy and cost-efficiency on simulations of forest management planning has not been evaluated. The aim of the present study was to analyse the effect of data acquisition accuracy on standwise forest inventory by comparing the accuracy and cost of traditional compartmentwise inventory methods with 2D and 3D measurements of digital aerial photographs and airborne laser sca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
29
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
6
2

Relationship

4
4

Authors

Journals

citations
Cited by 33 publications
(29 citation statements)
references
References 28 publications
0
29
0
Order By: Relevance
“…The errors observed in stand-level field inventory and area-level ALS estima-tion were characterised using three error properties: error trend, error distribution shape and correlations between the errors. In most previous studies, the errors have been assumed to be normally distributed and uncorrelated (Eid 2000, Holopainen & Talvitie 2006. According to Paper III, this assumption may be invalid.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The errors observed in stand-level field inventory and area-level ALS estima-tion were characterised using three error properties: error trend, error distribution shape and correlations between the errors. In most previous studies, the errors have been assumed to be normally distributed and uncorrelated (Eid 2000, Holopainen & Talvitie 2006. According to Paper III, this assumption may be invalid.…”
Section: Discussionmentioning
confidence: 99%
“…The average inoptimality losses relative to stand-level NPV ranged from 4.5% to 6.4%, depending on the error simulation method. Holopainen & Talvitie (2006) reported inoptimality losses ranging from 4.2% to 11.4%, depending on the simulated forest inventory method. The inoptimality losses reported by Eid (2000) were considerably smaller than in this study (on average 0.92%) but the distributions of random errors were also narrower.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This aspect can be studied using cost-plus-loss analyses, in which the expected losses due to suboptimal decisions are added to the total forest inventory costs ( [16,17]). The cost-plus-loss approach was widely utilized in recent forest inventory-and planning-related research (e.g., [18][19][20][21][22][23][24]). …”
Section: Introductionmentioning
confidence: 99%
“…For example, an error in the inventory data can lead to the early final cutting of a stand (Eid 2000). Holopainen and Talvitie (2006) also studied the effect of errors in inventory data on the expected net present value (NPV). They found that the NPV losses were different for different types of inventory methods.…”
Section: Introductionmentioning
confidence: 99%